Ethical issues in e-learning. - Zeki, Ahmed M.; Zeki, Akram M.; Hameed, Shihab A. (IIUM Press, 2011)
E-Iearning is becoming a fast growing sector of higher education. Although there are many advantages of e-Iearning, yet there are some ethical issues related to e-Iearning. This paper provides a general overview of such ethical issues. It also provides some strategies to overcome them.